Failed Medical Management of a Caesarean Scar Pregnancy Leading to Manual Vacuum Aspiration and Hysterotomy: A Case Report (Community Based Medical Journal, 2025)
Caesarean scar pregnancy (CSP) is a unique type of pregnancy that has been becoming more common due to the growing cesarean section rate. This case report is about a 36-year-old woman with Caesarean scar pregnancy who did not respond to medical management and later underwent successful surgery. The patient previously had two Caesarean section deliveries and three abortions; she was initially given two cycles of methotrexate. However, measurement of β-hCG titers and sonography established continuation of pregnancy at 9 weeks±3 days. Another attempt at medical management with misoprostol and mifepristone was also unsuccessful. Elevation of the β-hCG level was observed from 4165 mIU/mL to 33526 mIU/mL within a month, which was suggestive of a continuing pregnancy. Following those failed medical interventions, a manual vacuum aspiration (MVA) was also tried and failed. For further safety and wellbeing of the patient, hysterotomy under general anaesthesia was done. The case highlights several critical aspects of CSP management: monitoring in the form of serial β-hCG and ultrasound, the shortcomings of medical management, and the timing of the transition to surgery. The fact that performing MVA and hysterotomy after failed medical management signifies that healthcare settings should have more than one treatment options in such cases. Altogether, this paper adds to the number of studies on the management of CSP, highlighting tailored therapeutic methodologies and the importance of the follow-up period. It is the same way that it also poses a challenge regarding the timing of treatment intervention and stressing patient counsel on future pregnancy dangers after a cesarean section.  CBMJ 2025 January: Vol. 14 No. 01 P: 163-167